Estudo de cargas térmicas de uma aeronave e dimensionamento de um sistema de ar condicionado - Guimarães, Maria Fernanda Gayer [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work deals with the thermal load study of a fictitious aircraft as well as scaling, in terms of the airflow and temperature of the air conditioning system, for heating and cooling of the its internal environment, aiming the thermal comfort of occupants. The first part is presented the techniques and methods utilized for modeling different heat exchanges that occur in the aircraft and then allowed to calculate the total heat load and the airflow and temperature necessary to comply with the requirements of the thermal comfort. Techniques to determine the basic parameters, as convection coefficient and global coefficient of heat exchange, are also presented. The work aims to develop a program, using a computational tool, to automate the calculations so that facilitate this study. It also allows to be used for other airplanes just changing parameters and the control variables related to the specific project. Finally the program performs calculations for a fictitious airplane, to analyze its functionality and the influence of parameters involved in the temperature controls. The program allowed analyzing the sensitivity of portions of the thermal load and the corresponding parameters of influence, as well as the scaling of the air conditioning in terms of airflow and temperature. It was considered, despite the simplifications, a good approximation to the actual values and then can be used in development of the other airplanes

Esse trabalho trata da análise de cargas térmicas de uma aeronave modelo assim como o dimensionamento, em termos de vazão e temperatura, do sistema de ar condicionado para a refrigeração e aquecimento do ambiente interno de modo manter o conforto térmico dos ocupantes. Primeiramente são apresentados técnicas e métodos utilizados para a modelagem das diferentes trocas de calor que ocorrem na aeronave e assim calcular a carga térmica total e então a vazão e a temperatura necessária do sistema para atender os requisitos de conforto térmico. Também são apresentadas técnicas para calculo de parâmetros básicos, por exemplo, o coeficiente de película e coeficiente global de transferência de calor. O trabalho visa desenvolver um programa, usando uma ferramenta computacional, para automatizar os cálculos de modo que ele facilite esse estudo, o qual poderá ser usado em outras aeronaves alterando apenas os dados específicos do projeto e as respectivas variáveis de controle. Por fim o programa é aplicado em uma aeronave modelo com a finalidade de analisar sua funcionalidade e a influência das variáveis relacionadas ao controle de temperatura. O programa permite analisar a sensibilidade das parcelas da carga térmica total e os respectivos parâmetros de maior influência, assim como o dimensionamento do ar condicionado em termos de vazão e temperatura e foi considerado, apesar das simplificações, uma boa aproximação em relação aos valores reais podendo ser usado no desenvolvimento de outras aeronaves
Keywords: Refrigeração; Ar condicionado; Carga termica; Aeronaves; Thermal load; Air Conditioning System; Aircraft